Analysis of Tube Leakage of X-Ray Radiation Using Geiger Muller Sensor Equipped with Data Storage - Bedjo Utomo; Tribowo Indrato; Her Gumiwang Ariswati; Urip Mudjiono; Bayu Ardiansyah; A K M Bellal Hossain; Klarnarong Wongpituk (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2022)
X-ray radiation (ionization) cannot be felt directly by the five human senses. Therefore, radiation monitoring is needed, one of which by using a survey meter. The purpose of this research is to directly monitor the level of radiation exposure and leakage of X-ray tube containers in the work area. This was done to ensure the safety and health of workers in the radiation transmission area, so that it is in accordance with the ALARA (As Low As Reasonably Achievable) principle, which is stipulated in the Decree of the Minister of Health RI No. 1250/Menkes/SK/XII/2009 concerning Guidelines for Quality Control of Radiodiagnostic Equipment as Standard Values ​​for X-Ray Radiation Monitoring. This research is an experimental study with a survey meter equipment module design using a Geiger Muller sensor equipped with data storage. This module design method uses Arduino programming as data processing and is displayed on the CHARACTER LCD. Test analysis was carried out by comparing the measurement value of the module with the standard value as a standard for comparison. Based on the measurement results, the X-ray tube leak test value resulted in a standard AAT survey meter value of 0.001 both using a closed and unsupplied 2mm Pb circuit, namely 0.00097 mGy/hour and 0.00092 mGy/hour. Meanwhile, the results of the tube leakage test using a survey meter, both circuits, modules, and standard survey meters show a passing grade test value of < 1mGy/hour. In conclusion, the module design using the Geiger Muller sensor is feasible to use.